Architectural Design by Considering Communication Systems with Observer (Case Study: KLIA Internasional Airport) - Imam Faisal Pane; Hilma T Fachrudin; Hesti Fibriasari; Aurora S Lubis (Britain International of Exact Sciences (BIoEx) Journal, 2020)
The development of architecture along with the development of situations and conditions that exist in the community. In this postmodernism era, architectural design is not only based on one paradigm, but is more free to choose the architectural design figure that will be achieved. The development of this infinite design can be studied or appreciated through a communication approach between an architectural object and an observer. The architectural design of this era can have different meanings among observers. This proves that the communication system does not guarantee the meaning of a building. This system only runs that the building can be interpreted based on a communication system in the form of a sign like the one in Semiotics. Using qualitative and quantitative descriptive methods in seeing the current development of architecture. This gives the conclusion that architectural design not only has a meaning but many meanings in accordance with the design paradigm used.